2016
DOI: 10.1016/j.celrep.2016.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Central Insulin Action Activates Kupffer Cells by Suppressing Hepatic Vagal Activation via the Nicotinic Alpha 7 Acetylcholine Receptor

Abstract: Central insulin action activates hepatic IL-6/STAT3 signaling, which suppresses the gene expression of hepatic gluconeogenic enzymes. The vagus nerve plays an important role in this centrally mediated hepatic response; however, the precise mechanism underlying this brain-liver interaction is unclear. Here, we present our findings that the vagus nerve suppresses hepatic IL-6/STAT3 signaling via α7-nicotinic acetylcholine receptors (α7-nAchR) on Kupffer cells, and that central insulin action activates hepatic IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 42 publications
(62 reference statements)
2
67
0
Order By: Relevance
“…The expression of the capsaicin-sensitive TRPV1, which is frequently co-localized with TRPA1, is commonly associated with this subtype of vagal sensory neurons (Nassenstein et al, 2008; Mazzone and Undem, 2016; Kollarik et al, 2010). These fibers with cell bodies in both the nodose and jugular ganglia, have different molecular phenotypes and central locations and are associated with different physiological responses (Kimura et al, 2016). The expression of Nav1.7, Nav1.8, and Nav1.9 has also been determined in vagal sensory neurons of nociceptor type, specifically in airways (Mazzone and Undem, 2016).…”
Section: The Immune Impact On Afferent Neuronal Functionmentioning
confidence: 99%
“…The expression of the capsaicin-sensitive TRPV1, which is frequently co-localized with TRPA1, is commonly associated with this subtype of vagal sensory neurons (Nassenstein et al, 2008; Mazzone and Undem, 2016; Kollarik et al, 2010). These fibers with cell bodies in both the nodose and jugular ganglia, have different molecular phenotypes and central locations and are associated with different physiological responses (Kimura et al, 2016). The expression of Nav1.7, Nav1.8, and Nav1.9 has also been determined in vagal sensory neurons of nociceptor type, specifically in airways (Mazzone and Undem, 2016).…”
Section: The Immune Impact On Afferent Neuronal Functionmentioning
confidence: 99%
“…Nicotine is an alkaloid naturally produced by the tobacco plant that binds nicotinic acetylcholine receptors, found throughout neuronal and non-neuronal or visceral organs. These receptors participate in signaling within the central and peripheral nervous system and in a number of metabolic tissues, including pancreatic islets, adipose tissue, macrophages, liver, and skeletal muscle [1417]. Nicotine has been shown to directly alter glucose homeostasis [18], suggesting an important role for this additive in the development of T2D.…”
Section: Smoking Leads To a Variety Of Chemical Exposuresmentioning
confidence: 99%
“…These events eventually reduce HGP via the STAT3-mediated downregulation of genes such as glucose-6-phosphatase ( G6pc ), a gluconeogenic enzyme [79,80]. Recently, Kimura et al [81] demonstrated that the inhibition of hepatic gluconeogenic enzymes in response to central insulin signaling is mediated by the α 7 -nicotinic acetylcholine receptor (Fig. 1).…”
Section: Hypothalamic Insulin Signaling and The Regulation Of Hepaticmentioning
confidence: 99%